Political Stability in Absence of Violence and Economic Growth in Pakistan - Javed, Zahoor Hussain; Waseem, Liaqt Ali; Shabbir, Muhammad; Mushtaq, Abdul Qadir (Journal of History Culture and Art Research, 2018)
This snapshot of political stability in absence of violence (POLIT) and economic growth (ECG) is analyzed in this study for period 1980-2016. The Ng-Perron is used to determine to order of integration. The findings shows that both series are integrated of order one. The short run impact of political stability in absence of violence on economic growth in Pakistan is determined by using VAR test and long term relationship is determined with help of Johansen Cointegration technique. This test point out that both series are integrated of order one. The impulse response functions show that there is a positive and significant short-run association between economic growth and political stability in absence of violence. Further, analysis Granger causality test showed that there was a unidirectional causality from POLIT to ECG. Policies that will assist in the control of violence and other regulatory measures are recommended to boost up economic growth in Pakistan.